Psychological capital intervening effect on individual competency and educator accountants’ research performance in Surabaya - Fitriyah Kusuma Devi; Bambang Tjahjadi (STIE Perbanas Surabaya, 2020)
This research aimed to discover the effects of knowledge, skill, and attitude on educator accountants’ research performance with psychological capital as an intervening variable. The Research object was educator accountants with their full-time status at both public and private higher education in Surabaya. The sample was taken by means of purposive sampling and it gained 167 employees. The data were analyzed using Structural Equation Modeling (SEM). The result shows that: (1) knowledge, skill, and attitude significantly affect educator accountants’ performance in Surabaya. (2) Psychological capital within educator accountants also significantly intervenes in the relationship between skill and attitude on educator accountants’ performance in Surabaya. However, psychological capital does not intervene relationship between knowledge on educator accountants’ performance in Surabaya.